A global common good: improving financing for UN humanitarian aid - Reinhardt, Dieter (Friedrich-Ebert-Stiftung, 2019)
This publication analyses the global funding for humanitarian aid, which is insufficient, while existing aid resources are often not employed according to needs. The author explains how geostrategic regional priorities of influential governments affect the UN humanitarian aid system. The publication discusses reform proposals, including a mandatory humanitarian budget, similar to the assessed contributions of Member States to the UN's peacekeeping budget. Such an arrangement could lead to greater financial independence for UN humanitarian agencies and it would also establish the prevention of existential humanitarian crises as a global common good.
Keywords: Vereinte Nationen; Erde